Integrated Care for Complex Patients A Narrative Medicine Approach (Springer International Publishing, 2018)
This book presents case-based descriptions of models for the inclusive, multispecialty and multidisciplinary clinical care of complex cases. Cases range from primary care patients with complex systemic medical and psychiatric comorbidity, to those requiring specialty care, to those with potentially terminal illnesses. While each category and case has its unique requirements often necessitating different models of care, the commonalities in approaching complex clinical situations is underscored. Extended case narratives written by the treating physicians, summarizing both the course of clinical care and physicians' reflections on the challenges of managing complex patients, comprise the bulk of the book. Five additional chapters on systems issues associated with care of complex patients, together with a chapter on end of life considerations, a narrative analysis of the physicians reflections about complex patients, and a concluding chapter are prominently included to anchor the case narratives. Written by experts in the field, these descriptions form unique models for assessing and treating complex cases. Integrated Care for Complex Patients is a useful guide for all health practitioners and health administrators who are responsible for clinically complex cases, including physicians in primary care and psychiatry, physician assistants and nurse practitioners, and psychologists.